Kinetic Mechanism Reduction Using Genetic Algorithms, Case Study on H2/O2 Reaction - Hossein Abedini; Mahmoud Reza Pishvaie; Ramin Bozorgmehry Boozarjomehry (Iranian Journal of Chemistry & Chemical Engineering, 2007)
For large and complex reacting systems, computational efficiency becomes a critical issue in process simulation, optimization and model-based control. Mechanism simplification is often a necessity to improve computational speed. We present a novel approach to simplification of reaction networks that formulates the model reduction problem as an optimization problem and solves it using genetic algorithm (GA).The aim of simplification kinetics modeling is to derive the simplest reaction system, which retains the essential features of the full system. Numerical results for H2/O2 combustion reaction mechanism illustrate the potential and proficiency of this approach.